Discovering Mathematics: A Quantitative Reasoning Approach - Richard N. Aufmann (Cengage Learning, 2018)
Aufmann's DISCOVERING MATHEMATICS: A QUANTITATIVE REASONING APPROACH with WebAssign helps you learn mathematics in the context of the world around you. Focusing on topics relevant to your life and developing critical-thinking skills that you can apply beyond the course, this text provides you with exactly what you need for the world around you in an approachable, engaging and streamlined format. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.